Corporate Governance and Voluntary Disclosure: Literature Study and Summary of Empirical Studies - Rochmah Darmayanti, Indriati (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to analyze and summarize empirical studies from several journal articles that have been obtained. The sample in this study consisted of 10 journal articles from 2022-2015. The methods used are literature study and empirical study summaries. This study concludes that corporate governance is often used in research related to voluntary disclosure, namely Board Size and Audit Committee Size. This proves that the size of the Board and the Size of the Audit Committee can increase the extent of voluntary disclosure. When viewed from an assignment perspective, the size of the Board is tasked with managing the Company as a whole, so it is not surprising that it plays an important role in the extent of voluntary disclosure. Meanwhile, the Audit Committee is tasked with reviewing the financial statements issued by the Company to the public and interestingly, the Audit Committee is elected or dismissed directly by the Board of Commissioners, so it is not surprising that it plays an important role in the extent of voluntary disclosure.